2013
DOI: 10.1534/g3.113.006023
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Profiling of Nuclear Receptor Transcription Patterns over the Course ofDrosophilaDevelopment

Abstract: Previous work has shown that many of the 18 family members of Drosophila nuclear receptor transcription factors function in a temporal hierarchy to coordinate developmental progression and growth with the rate limiting process of metabolism. To gain further insight into these interactions and processes, we have undertaken a whole-family analysis of nuclear receptor mRNA spatial expression patterns over the entire process of embryogenesis, as well as the 3rd instar wandering larva stage, by using high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…In another example, the polarized distribution of Hsp83 transcripts on one side of the nucleus (Fig. 3E) looks remarkably similar to a number of nuclear receptor transcripts, which we previously colocalized together with subregions of ER (Wilk et al 2013). This colocalization could be associated with the known roles of Hsp83 as a chaperone and regulator of nuclear receptor folding and function, with perhaps an additional level of regulation at the level of translation.…”
Section: New and Prevalent Subcellular Distribution Categoriessupporting
confidence: 77%
See 3 more Smart Citations
“…In another example, the polarized distribution of Hsp83 transcripts on one side of the nucleus (Fig. 3E) looks remarkably similar to a number of nuclear receptor transcripts, which we previously colocalized together with subregions of ER (Wilk et al 2013). This colocalization could be associated with the known roles of Hsp83 as a chaperone and regulator of nuclear receptor folding and function, with perhaps an additional level of regulation at the level of translation.…”
Section: New and Prevalent Subcellular Distribution Categoriessupporting
confidence: 77%
“…Indeed, these biochemical approaches have suggested that as much as 50% of cytosolic protein-encoding transcripts are translated on ER (Reid and Nicchitta 2012;Jagannathan et al 2014). We also showed previously, using double labeling, that transcripts encoding transcription factors can also be enriched and translated on ER (Wilk et al 2013), suggesting that ER localization may be a common means of localizing transcripts that encode numerous types of proteins. In the case of the nuclear receptor transcripts that we found to be associated with ER, this may provide a number of advantages, including proximity to the nucleus, proximity to translational regulators and chaperone cofactors (e.g., Hsp83 RNA also appears to be similarly localized), or proximity to ER-derived ligands (e.g., the E75 ligand heme is enriched in ER) (Reinking et al 2005).…”
Section: Subcellular Localization Prevalencesupporting
confidence: 67%
See 2 more Smart Citations
“…The three LdE75 s were detectable in all tested larval tissues. Similar expression profiles of Nuclear receptors (NRs) have been found in the same 20E‐response tissues in other insect species (Fahrbach et al ., ; Wilk et al ., ). Interestingly, our results revealed that the expression levels of LdE75A and LdE75C were lower than that of LdE75B in the L. decemlineata PGs.…”
Section: Discussionmentioning
confidence: 97%